PENGARUH ORIENTASI PASAR, ORIENTASI KEWIRAUSAHAAN DAN KAPABILITAS PEMASARAN TERHADAP KINERJA PEMASARAN PADA UMKM BERBASIS AGRIBISNIS DI KABUPATEN TANGERANG - Silvia Diah Arumsari; Meutia Meutia; Asih Mulyaningsih (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2023)
The increase in the number of MSMEs during the Covid pandemic in 2018-2021 in in contrast to the value of regional original income (PAD) in 2019 - 2020 which decreased. Data obtained from Tangerang Regency in numbers shos that the amount of PAD in 2018 wa s Rp. 2,872,568,512.69 decreased in 2019 to Rp. 2,806,539,756.44 and its value decreased again in 2020 to Rp. 2,500,580,661.48. The drastic decline in regional original income from 2018 to 2020 indicates thet there are problems in the development of agribusiness-based MSMEs in Tangerang Regency. This study aims to analyze market orientation, entrepreneurial orientation, marketing capability on marketing performance in agribusiness-based SMEs in Tangerang Regency. The research was structured as explanatory research with a quantitative approach using descriptive analysis with smartPLS software, while the analytical method used Structural Equation Modeling (SEM) with a total of 89 MSME respondents in Pasarkemis and Rajeg sub-districts. Based on the result of data processing on the agribusiness-based MSME marketing perfomance model in Tangerang Regency, it can be concluded that marketing capability is the entrepreneurial orientation variable, the indicators for the entrepreneurial orientation variable that have the most influence are innovation, proactivity, risk taking and autonomy. Market orientation and entrepreneurial orientation have a direct effect on marketing performance indicators on market orientation variables that give influence are customer orientation and coordinatoan between functions. The managerial implications that can be suggested by this research are pilicies that focus on customer oriantation towards MSME actors. This study provides several research limitation than can be carried out in further research.